2007
DOI: 10.1590/s1807-59322007000500004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen-Progestin Hormonal Replacement Therapy on Blood Coagulation and Fibrinolysis in Postmenopausal Women

Abstract: Tests were performed before (T0) and after 3 (T3), 6 (T6) and 12 (T12) months of treatment. AT was determined by an amidolytic method, whereas F1+2 and TAT complex were measured by ELISA. RESULTS: There was a significant reduction in the AT level of patients who received oral CEE plus MP at T3. There was no AT reduction in patients taking either oral CEE alone or transdermal 17beta-estradiol plus MP. F1+2 increased in all patients, but it reached statistical significance only in patients receiving transdermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…In the group in which the flat edge of the retail was turned into the aorta this phenomenon was more intense on the suture line and was related to the roughness of the area and local release of thromboplastin by damaged tissues. Our results suggest that the wrinkled face of the retail would facilitate the capture and adhesion of blood components across its surface, with subsequent assemblage by the release of platelet factors and secondarily by thromboplastin released from damaged tissues [19]. We also verified that in this group there was the formation of a thin inner cover layer, resulting in dilatation of the patch area of surgery.…”
Section: Discussionsupporting
confidence: 67%
“…In the group in which the flat edge of the retail was turned into the aorta this phenomenon was more intense on the suture line and was related to the roughness of the area and local release of thromboplastin by damaged tissues. Our results suggest that the wrinkled face of the retail would facilitate the capture and adhesion of blood components across its surface, with subsequent assemblage by the release of platelet factors and secondarily by thromboplastin released from damaged tissues [19]. We also verified that in this group there was the formation of a thin inner cover layer, resulting in dilatation of the patch area of surgery.…”
Section: Discussionsupporting
confidence: 67%
“…Generally, Fib concentration in blood serum increases with age but this increase is smaller in women with hormonal replacement therapy in postmenopausal age [5,18,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…According to many studies the influence of hormonal replacement therapies on C and S Proteins and AT III is different [2,5,6,7,12,18,24,26]. Some authors noted the increase of protein C and S [12,20] but others observed decrease of these natural coagulation inhibitors [Fishman et al 2003].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies, which most of them were randomized controlled trials, were adequately designed for assessing the effect of progestogens or for comparing the effect of a specific progestogen to each other on APCr, a validated surrogate marker of VTE and on F1+2 or Ddimers, first-generation biomarkers of coagulation and fibrinolysis [29,33,40,41,43,[47][48][49][50][51]53] (table 2). In addition, because postmenopausal women using progestogens are also prescribed estrogens, it is important to note that the influence of progestogens on haemostasis among postmenopausal women has been only investigated in a context of estrogens use.…”
Section: Progestogens and Haemostatis: Biological Studiesmentioning
confidence: 99%
“…On one hand, some data allowed assessing the main effect of some progestogens by comparing the changes in haemostasis between users of oral estrogens alone or combined with either micronized progesterone [51], dydrogesterone [33,40] , MPA [29,47,51], trimegestone [33,40] or gestodene [43]. Micronized progesterone, dydrogesterone, MPA and trimegestone may not induce significant changes in F1+2, DDimers and APCr related to oral estrogens use.…”
Section: Progestogens and Haemostatis: Biological Studiesmentioning
confidence: 99%